(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Soil microbial biomass (BMS), CO2 emissions, and organic carbon (Corganic) contents were quantified in soils with different anthropogenic uses in the "Bosque Protector Murocomba" (BPM). Five land use scenarios (treatments) were established (primary forest, secondary forest, fallow, plantation of Gmelina arborea, and pasture), within the Murocomba Protective Forest. Three soil samples were collected pertreatment. Induced substrate respiration technique was employed using glucose as inducer, streptomycin and chloramphenicol to inhibit bacterial populations, cycloheximide and captan 80 as fungal inhibitors. The CO2 released was trapped in NaOH solution (0.1 M) and titrated with HCl (0.1 M). Total Corganic contents, active microbial biomass and CO2 emissions were higher in the primary forest soil: 20.0 mg kg-1, 6.7 mg C-microbial g-1 dry soil (mg C-mic g-1 ss), and 50.4 mg CO2 100 g-1 s hour-1. Grassland soils generated lower contents: 12.5 mg kg-1, 2.1 mg C mic g-1 ss, and 15.9 mg CO2 in 100 g-1 s hour-1, respectively. In all soils, fungal biomass predominated over bacterial biomass. These results demonstrate that the soils of the BPM are important reserves of organic C, however, anthropogenic activities generate changes in the dynamics of the BMS in these natural forests of the western foothills of the Andes, causing alterations in nutrient cycling. This research constitutes a baseline that places the BPM as a control point for future regional or global biogeochemistry studies